Catalytical degradation of industrial dyes using biosynthesized selenium nanoparticles and evaluating its antimicrobial activities - Soumya Menon; Happy Agarwal; Venkat Kumar Shanmugam (Sustainable Environment Research, 2021)
Abstract The release of textile dyes from the industries to the environment has become a significant health issue to humans and their surroundings, where a large number of dyes are wasted to the nearby water during the dyeing process. Therefore, the practice of the utilization of biosynthesized nanoparticles from numerous biological systems has been described, out of which plant material is considered the most appropriate method. The usage of plant material not only makes the procedure ecological but also their abundance makes it more cost-effective. The present study aims to biologically produce selenium nanoparticle using Mucuna pruriens seed powder and apply it in the degradation of dyes and removal of pathogenic bacterial cultures from pathogen-containing lake water using an optimum concentration of selenium nanoparticles. The production of selenium nanoparticles was characterized via visual coloration from colorless to brown solution which was checked using UV–Visible spectrophotometer, the crystalline structure was analyzed using X-ray diffraction, the morphology was analyzed with transmission electron microscopy, scanning electron microscopy, dynamic light scattering, which was in the range of 90–120 nm, with stable spherical monodisperse characteristics. The surface potential was checked using zeta potential, while the Atomic Force Microscopy gave information on the roughness of the nanoparticles, and the presence of –OH, −COO, aromatic groups were confirmed with Fourier Transform Infrared spectroscopy. The biosynthesized nanoparticles were then analyzed for its environmental applications, like degradation of dyes from industrial wastes and checking its antimicrobial activities.